TWO NEW SPECIES OF PLEUROTHALLIDINAE FROM CLOUD FOREST REMNANTS IN THE EASTERN ANDES OF COLOMBIA - Morales, Nicolás Gutiérrez [UNESP]; Moreno, Juan Sebastián; Alegría-Valencia, Melisa; Gil-Amaya, Karen (Universidad de Costa Rica, 2024)
Two new pleurothallid species of the genera Lepanthes and Pleurothallis, native to cloud forest remnants of the Eastern Andes of Colombia, are described and illustrated. Lepanthes pseudoabitaguae is compared with Lepanthes abitaguae, from which it differs by the color of the flowers and by the oblong and biglandular appendix. Pleurothallis falcata is similar to Pleurothallis suspensa, but can be recognized by the falcate to lanceolate leaves, denser inflorescences, longer sepals, and the lip completely recurved with erose apical margins. We also provide comparisons with similar species and offer comments on their ecology. Furthermore, we discuss the significance of this highly anthropized region and its richness in orchid species. Resumen. Se describen e ilustran dos nuevas especies de Pleurothallidinae de los géneros Lepanthes y Pleurothallis, nativas de remanentes de bosque nublado en los Andes Orientales de Colombia. Lepanthes pseudoabitaguae se compara con Lepanthes abitaguae, de la cual difiere por el color de las flores y por el apéndice oblongo y biglandular. Pleurothallis falcata es similar a Pleurothallis suspensa, pero puede ser reconocida por las hojas falcadas a lanceoladas, inflorescencias más densas, sépalos más largos y el labelo completamente recurvo con márgenes apicales erosas. También proporcionamos comparaciones con especies similares y ofrecemos comentarios sobre su ecología. Además, discutimos la importancia de esta región altamente antropizada y su riqueza en especies de orquídeas.
Keywords: endemism; endemismo; flora de Colombia; flora of Colombia; Lepanthes; Pleurothallis; taxonomy; taxonomía